2014
DOI: 10.1111/ene.12573
|View full text |Cite
|
Sign up to set email alerts
|

The association between chronic obstructive pulmonary disease and dementia: a population‐based retrospective cohort study

Abstract: This study shows that COPD is associated with a subsequent higher risk of dementia after adjusting for comorbidities. Specifically, the association between COPD and dementia is greater in patients with more frequent acute exacerbation events of COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(69 citation statements)
references
References 35 publications
4
63
2
Order By: Relevance
“…48.5 % of COPD patients were reported to have cognitive impairment (Incalzi et al 1993). Recently, prospective studies confirm that COPD increases the risk of mild cognitive impairment (MCI) and dementia (Liao et al 2015;Singh et al 2013Singh et al , 2014. However, the molecular mechanism for the association of COPD and its risk of dementia is still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…48.5 % of COPD patients were reported to have cognitive impairment (Incalzi et al 1993). Recently, prospective studies confirm that COPD increases the risk of mild cognitive impairment (MCI) and dementia (Liao et al 2015;Singh et al 2013Singh et al , 2014. However, the molecular mechanism for the association of COPD and its risk of dementia is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive impairment, more prevalent among COPD patients (Antonelli-Incalzi et al 2007), has been viewed as one of the important extrapulmonary manifestation in patients with COPD (Ortapamuk and Naldoken 2006). Recently, a nationwide retrospective cohort study demonstrated that COPD is associated with increased risk of dementia (Liao et al 2015). However, the molecular event underlying is still not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The risk of depression was elevated fourfold among those with a COPD-related hospitalization [5]. COPD may also increase risk for dementia [6]. And depending on the extent of patient dependency, caregivers of persons with COPD have elevated rates of health-related problems [7].…”
Section: Chronic Obstructive Pulmonary Diseasementioning
confidence: 99%
“…Cognitive decline is common in severe congestive heart failure [26] and heart disease overall [27]. Chronic obstructive pulmonary disease (COPD) is also associated with dementia, especially in patients with frequent exacerbations [28]. Chronic kidney disease is independently associated with all-cause dementia in patients with vascular risk factors [29].…”
Section: Introductionmentioning
confidence: 99%